Rivaroxaban Experience at Tertiary Care Centre in Saudi Arabia:A Retrospective Observational Study: - Riazuddin, Muhammad; Ahmed Mpharm, Mohamed; Butt, Muhammad Imran; Khan, Shahid Masud; Abufarhaneh, Muhammad; Emadi, Omar; Alshammari, Khalid; Alsudairy, Haifa Fahad; Alkasab, Muhammad; Sheikh, Aamir; Alrashed, Abdulaziz (Galen Medical Journal, 2020)
Background: Atrial fibrillation (AF) and Venous Thromboembolism (VTE) are significant causes of morbidity and mortality. Direct oral anticoagulants (DOACs) are as effective as vitamin K antagonists (VKAs) with a propensity to cause less major bleeding. This study aimed to assess the safety and effectiveness of rivaroxaban in routine clinical practice in a large tertiary referral center in Saudi Arabia. Methods and Materials: In this study, patients who received rivaroxaban at a tertiary referral hospital were included in this study. All adverse events were recorded, including major bleeding, non-major bleeding events, symptomatic thromboembolic events (deep vein thrombosis, pulmonary embolism) and all-cause death. Results: A total of 509 patients were prescribed rivaroxaban during the study period. The most common indication for rivaroxaban was non-valvular AF (65.3%) and VTE (34.7%). The mean age was 60.4 Â± 16.4 years, and 50.8% were female. The median CHA2DS2-Vasc score was 2.1 in patients on rivaroxaban for non-valvular AF. Bleeding occurred in 72 (14.1%) patients, of which 20 (3.9%) had major bleeds. Thrombosis events occurred in 13 (2.5%) patients in the overall cohort. Fourteen (2.7%) patients died during the study, including a case of fatal bleeding secondary to rivaroxaban. Conclusion: This study describes the use of rivaroxaban in a broad patient population in clinical practice in the Middle East. The overall bleeding and thrombosis rates in this study were comparable to those seen in major clinical trials. [GMJ.2020;9:e1882] DOI:10.31661/gmj.v9i0.1882